Liberdade de expressão artística: concepções filosóficas, fundamentalidade constitucional e política da pluralidade - Aguiar, Ana Cláudia da Costa (2013)
The right to artistic expression, freedom granted in the western democratic constitutionalism, is a fundamental right that cyclically, compared to other cohesive rights of expression, has been forgotten and put in an irrelevant juridical-dogmatic position. The first reason for this behaviour that disesteems artistic freedom is the valorisation of rationalism and scientificism in the modern society, subordinating academic researches to utilitarianism, relegating the purpose of feelings and spirituality on men s elocution, therefore, we investigate, guided by philosophy, the attribution of art on human formation, due to its capacity in harmonising reason and emotion. After that, we affirm the fundamental right to artistic expression s autonomy in the 1988 valid constitutional order, after a comparative explanation of freedom in the Fundamental Laws of United States, Portugal, Spain and Germany; and the construction historic-constitutional of the same right in the Brazilian Constitutions. In this desiderate, the theoric mark chosen is the Liberal Theory of the fundamental rights, guiding the exam through jusfundamental dimensions: juridical-subjective and juridical-objective. Whilst the first, classical function of resistance, delimitates the protection area of the artistic expression right from its specific content, titularity and its constitutional and subconstitutional limits, the other one establishes it as cultural good of the Social Order, defining to the State its rendering duties of protection, formation and cultural promotion. We do not admit artistic communication, granted without legal reserve, to be transposed of restrictions that belong to other fundamental rights and, when its exercise collides with another fundamental right or juridical-constitutional good, the justification to a possible state intervention that tangentiates its protection area goes, necessarily, through the perquisition of the artist s animus, the used method, the many viable interpretations and, at last, the correct application of the proportionality criteria. The cultural public politics analysis, nevertheless, observes the pluralism principle of democratic substratum, developer of the cultural dialogue and opposed to patterns determined by the mass cultural industry. All powers are attached, on the scope of its typical attributions, to materialise public politics that have the cultural artistic good as its aim, due to the constant rule contained in §1, art. 5º of the Federal Constitution. However, the access and the incentive laws to culture must be constantly supervised by the constitutional parameter of fundamental right to equality